1995
DOI: 10.1177/002194369503200304
|View full text |Cite
|
Sign up to set email alerts
|

A Review, an Integration, and a Critique of Cross-Disciplinary Research on Performance Appraisals, Evaluations, and Feedback: 1980-1990

Abstract: Performance related pay and the performance appraisal system continue to have a strong presence in corporate America. The presence of the performance appraisal system ranges from more traditional paper-and-pen systems to the emergence of eAppraisal, a web-based software designed by Halogen to facilitate the appraisal process. The current study investigates trends in this area. Ninety-eight empirical studies on performance appraisals, published between 1990 and 2000, in business, communication, and psychology j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 162 publications
2
40
0
Order By: Relevance
“…However, because it is believed that employees may have negative attitudes toward performance evaluations, sales managers may fear, postpone, or even discontinue performance appraisals (Thomas and Bretz, 1994;Wanguri, 1995). Yet if managers fail to conduct (or devote inadequate attention to) performance appraisals, the resulting loss of human resource development opportunities can be considerable.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, because it is believed that employees may have negative attitudes toward performance evaluations, sales managers may fear, postpone, or even discontinue performance appraisals (Thomas and Bretz, 1994;Wanguri, 1995). Yet if managers fail to conduct (or devote inadequate attention to) performance appraisals, the resulting loss of human resource development opportunities can be considerable.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they may conduct appraisals without sufficient preparation. An absence of a formal and well-prepared evaluation may cause employees to feel slighted in the appraisal process itself (Wanguri, 1995). Therefore, the first hypothesis examines the impact that the formality of the evaluation process (degree of structure) has on sales force satisfaction.…”
Section: Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, additional training of supervisors may increase the recognition and value of new or altered performance activities, particularly among police agencies that are implementing changes in strategies and tactics. Several studies had indicated that appraisal accuracy could be improved through rater training (Arvey & Murphy, 1998;Wanguri, 1995), and a number of researchers had affirmed that specific training approaches were linked with employee satisfaction in the appraisal process (Spears & Parker, 2002;Thomas, 1997;Wanguri, 1995). Additionally, there was evidence that employee development and coaching skills could be improved through evaluator training (Fink & Longenecker, 1998;Roberts & Reed, 1996) and that training might increase perceptions of procedural justice (Boswell & Boudreau, 2000;Roberts & Reed, 1996;Tang & Sarsfield-Baldwin, 1996).…”
Section: Rater Trainingmentioning
confidence: 99%